Factors Affecting Consumers’ Impulse Buying Behaviour in Social Commerce - Lai, Ting Yu (2019)
Nowadays, business model is dynamic and always evolving. All the business is going to develop online (e-commerce) and advertise their products through social media such as Facebook, Instagram, Twitter and YouTube. Since Taiwan is one of the country that using social commerce the most, it is important to know what causes impulse buying behaviour on social commerce. Although there are a lot of studies that is about impulse buying behaviour, there are limited research that combine ecommerce and social media Thus, the main objective of this study is to determine the factors that affect consumers’ impulse buying behavior in Taiwan. The method used in this research was quantitative analysis with a sample size of 300 people in Taiwan. The methods used to analyse the data were: descriptive test, reliability test, Pearson correlation, multiple regression and multicollinearity test. The results showed that convenience, user experience, product recommendation and promotion have the significant positive relationship with the impulse buying behavior on social commerce. The p-value of the variables are 0.006, 0.042, 0.000 and 0.000 respectively. Moreover, promotion is the most influential and important variable on impulse buying behavior in social commerce. Hence, this research addressed different factors towards impulse buying behavior on social commerce in Taiwan perspective.